Radiological features of psoriatic arthritis - Davis, Razaan (Division of Radiology, 2014)
Psoriatic arthritis (PsA) is an inflammatory arthritis associated with psoriasis. Psoriasis is a dermatological condition that affects 1-2% of the population. Approximately 10-15% of patients with skin manifestations of psoriasis develop PsA and 0.3-1% of the general population. Moll and Wright defined PsA as psoriasis associated with inflammatory arthritis and usually a negative serological test for rheumatoid factor (RF).